Representation of Verbal Violence in Afsoone Sabz: A Critical Discourse Analysis - Samira Habibi Mazaheri; Ferdows Aghagolzadeh (Critical Literary Studies, 2023)
The main objective of this study is to examine different layers of power relations between characters of Persian novels as represented by Afsoone Sabz utilizing Norman Fairclough’s critical discourse analysis framework (1996) which paves the way for decoding social structures that cause verbal abuse in Iran. To this end, Afsoone Sabz novel, written by Takin Hamzeloo, is chosen as the case study. It can be maintained that social structures like gender inequality, socioeconomic status differences, and class struggle determine verbal abuses in Persian. It is reasonable to argue that Hamzeloo uses her text to influence the audience (Iranians in general and Iranian women in particular) to be aware of social practices (gender inequality, socioeconomic status differences, class struggle and power relations) in an attempt to change, if not subvert, power relations (obtain gender equality and remove socio-economic inequality in Iran). The paper suggests that Hamzeloo uses othering strategy, as a powerful rhetorical tool, to portray the pessimistic outlook Iranian men hold about women through verbal abuse.